(untitled) (Research, Society and Development, 2021)
Systemic arterial hypertension (SAH) is a chronic disease linked to hereditary, economic and social factors, with a high prevalence in the black Brazilian population. Neglect in public health policies directed at the quilombola population generates important exposure to the onset of SAH and its underdiagnosis. In this sense, the present investigation aims to analyze the prevalence and factors associated with the underdiagnosis of arterial hypertension in quilombola adults from a Bahian region, Brazil. The study is characterized as cross-sectional, population-based, with a sample of 850 quilombolas from the Bahia region. Data were collected through a questionnaire applied in the form of an individual interview and blood pressure assessment. Sociodemographic variables, lifestyle and presence of arterial hypertension were also included. In the data analysis, descriptive statistics and Poisson regression procedures were used to determine the prevalence ratios (PR) and 95% confidence intervals (95% CI). The general prevalence of underdiagnosed SAH (SAH sub) was 24.8% and 29.2% self-reported the presence of diagnosed SAH. A statistically significant association was found between HASsub with sex, education, measured blood pressure (BP) time, smoking and drinking (p <0.05). So, HASsub is present in 1 in 4 quilombola adults and is associated with sociodemographic factors (women and advanced ages), preventive behavior (BP measured at <1 year) and related to the health situation (not being overweight). These findings demonstrate the need for health care and health promotion practices, in addition to mechanisms adopted to prevent the disease.